Pengaruh BI Rate, Exchange Rate (IDR/USD), dan Inflasi terhadap Indeks Saham Syariah yang Tercatat di JII pada Pandemi Covid-19 Tahun 2020 - Isnaini Firdayanti; Achmad Agus Priyono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The economic reduction in Indonesian is marked by the weakening of stock index related to the COVID-19 pandemic, because investors are afraid to transact. This study intended to find the effect of the BI Rate, Exchange Rate, and Inflation on the Sharia Stock Index listed at JII during COVID-19 pandemic in 2020. This type of research is quantitative research with time series data. The population in this study is the index of companies that are included in the Islamic stock JII. The sample in this study is monthly data of the JII sharia stock index in January - December 2020. This study used secondary data with the technique of taking documentation methods, from the process of collecting, recording, and reviewing secondary data. The test results of multiple linear regression analysis show (1) simultaneously BI Rate, Exchange Rate, and Inflation affect the Sharia Stock Index at JII; (2)  partially BI Rate and Inflation have no effect on the Sharia Stock Index at JII, while the Exchange Rate has a negative effect on the Sharia Stock Index at JII. Keywords: BI Rate, Exchange Rate, Inflation, Sharia Stock Index, Jakarta Islamic Index.